HTML and CGI unleashed - December, John (Sams Net, 1995)
PC and Macintosh compatible CD-ROM includes: HTML examples in the book, CGI scripts that you can use for forms, guestbooks, searching, and more, Web development tools such as HTML editors, graphics, and Internet search and retrieval applications.